2023
DOI: 10.1002/acn3.51952
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional predictors of quality of life and functioning after COVID‐19

Mar Ariza,
Neus Cano,
Bàrbara Segura
et al.

Abstract: ObjectiveA long‐term decline in health‐related quality of life (HRQoL) has been reported after coronavirus disease 2019 (COVID‐19). Studies with people with persistent symptoms showed inconsistent outcomes. Cognition and emotion are important determinants in HRQoL, but few studies have examined their prognostic significance for HRQoL and functionality in post‐COVID patients with persisting symptoms. We aimed to describe QoL, HRQoL, and functioning in individuals post‐COVID with varying COVID‐19 severities and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
(204 reference statements)
1
0
0
Order By: Relevance
“…Although their cognitive evaluation was also based on extensive neuropsychological assessment, the authors concluded that cognitive performance was not associated with clinical characteristics or with frequently reported symptoms (including sleep problems) ( Bungenberg et al, 2022 ). Recently, quality of life has also been linked to slower mental processing speed, similar to our results, although sleep quality was not the focus of the previous research ( Ariza et al, 2023b ). However, these previous results confirm our findings on the relationship between sleep quality and processing speed, to which the mediating effect of quality of life may be added.…”
Section: Discussionsupporting
confidence: 87%
“…Although their cognitive evaluation was also based on extensive neuropsychological assessment, the authors concluded that cognitive performance was not associated with clinical characteristics or with frequently reported symptoms (including sleep problems) ( Bungenberg et al, 2022 ). Recently, quality of life has also been linked to slower mental processing speed, similar to our results, although sleep quality was not the focus of the previous research ( Ariza et al, 2023b ). However, these previous results confirm our findings on the relationship between sleep quality and processing speed, to which the mediating effect of quality of life may be added.…”
Section: Discussionsupporting
confidence: 87%
“…The pandemic exacerbated mental health issues, resulting in increased levels of depression and anxiety, which further deteriorate overall quality of life. Moreover, the disease affected various aspects of daily functioning, including mobility, cognitive function, and participation in life activities, with post-COVID symptoms exacerbating these issues [ 10 ].…”
Section: Introductionmentioning
confidence: 99%